Spatial distribution and risk factors associated with Salmonella enterica in pigs - Parada, J (2017)
Fil: Parada, J. Departamento de Patología Animal, Facultad de Agronomía y Veterinaria, Universidad Nacional de Río Cuarto; Argentina.